ANALISIS TINDAK PIDANA PEMERASAN DISERTAI DENGAN KEKERASAN YANG DILAKUKAN OLEH PREMAN DI POLRES LUWU - Salmi, Salmi; Rahman Nur, Abdul; Zakiah Drajat, Ulfah; Nasri, Nasri (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
In this case, the criminal act of extortion is committed by someone who feels he has the ability or power based on courage and claims in an area/territory that he has full authority. Perpetrators of criminal acts of extortion in this case in the Luwu area are termed thugs. Thugs carry out extortion because they think that they are someone who is brave (rewa) so they claim a place as their territory and anyone who carries out or seeks a livelihood in that place, is obliged to pay fees which in statutory regulations are called regional levies. The actions of these thugs are illegal because they are carried out by means of extortion accompanied by threats, unpleasant actions towards the local community, and irresponsibility. The fees collected by thugs are called thug quotas. This research was conducted with the aim of finding out the factors that cause the crime of extortion to occur and law enforcement efforts to overcome this problem.